Regulating a Firm under Adverse Selection and Moral Hazard in Uncertain Environment - Jing Feng; Yanfei Lan; Ruiqing Zhao (Abstract and Applied Analysis)
This paper investigates a problem of how to regulate a firm which has private information about the market capacity, leading to adverse selection, and which can increase the market demand by exerting costly effort, resulting in moral hazard. In such a setting, the regulator offers a regulatory policy to the firm with the objective of maximizing a weighted sum of the consumer surplus and the firm’s profit (i.e., the social total surplus). We firstly find that the regulator will set the firm’s effort level as zero under observable effort regardless of the market capacity being full or private information; that is, the effort has no impact on the optimal regulatory policy. Interestingly, we also show that, it is necessary for regulator to consider the difference between the effort’s impact on the demand and the price’s impact on the demand, which may generate different distortion effects about the regulatory policy.